Beauty and Meritocracy - Sarpila, Outi; Kukkonen, Iida (Springer, 2026)
This chapter discusses beliefs about beauty and meritocracy. We ask to what extent beauty is believed to be an individual merit and how these beliefs can contribute to beauty-based inequalities. We first review the basic idea of merit and meritocracy research, drawing on previous literature in socio-economics. As this research tradition has not examined people’s perceptions of beauty as merit, we turn to previous beauty and inequality research in this analysis. The literature review makes it clear that there is no unified view in the field of beauty and inequality research on the extent to which beauty can be considered an achieved or ascribed characteristic. Our empirical case, based on Finnish survey data, suggests that the best way to approach beauty as merit is to divide it into components and analyse them separately. In other words, the different components of appearance, and thus beauty, seem to be structured very differently along the ascribed-achieved continuum. In addition, our empirical case suggests that beliefs related to appearance seem to legitimize class-based and gender-based inequalities, in particular. At the end of the chapter, we present thoughts on how meritocracy research should include considerations of appearance-related characteristics and how researchers interested in appearance and inequality could better understand the phenomenon by taking into account the significance of prevailing societal beliefs.
Handbook of Beauty and Inequality